Staphylococcus aureus bloodstream infections in Latin America: results of a multinational prospective cohort study. (17th October 2017) - Seas, Carlos; Garcia, Coralith; Salles, Mauro J; Labarca, Jaime; Luna, Carlos; Alvarez-Moreno, Carlos; Mejía-Villatoro, Carlos; Zurita, Jeannete; Guzmán-Blanco, Manuel; Rodríguez-Noriega, Eduardo; Reyes, Jinnethe; Arias, Cesar A; et al.
Abstract: Background: Substantial heterogeneity in the epidemiology and management of Staphylococcus aureus bacteraemia (SAB) occurs in Latin America. We conducted a prospective cohort study in 24 hospitals from nine Latin American countries. Objectives: To assess the clinical impact of SAB in Latin America. Patients and methods: We evaluated differences in the 30 day attributable mortality among patients with SAB due to MRSA compared with MSSA involving 84 days of follow-up. Adjusted relative risks were calculated using a generalized linear model. Results: A total of 1030 patients were included. MRSA accounted for 44.7% of cases with a heterogeneous geographical distribution. MRSA infection was associated with higher 30 day attributable mortality [25% (78 of 312) versus 13.2% (48 of 363), adjusted RR: 1.94, 95% CI: 1.38–2.73, P  < 0.001] compared with MSSA in the multivariable analysis based on investigators' assessment, but not in a per-protocol analysis [13% (35 of 270) versus 8.1% (28 of 347), adjusted RR: 1.10, 95% CI: 0.75–1.60, P  =   0.616] or in a sensitivity analysis using 30 day all-cause mortality [36% (132 of 367) versus 27.8% (123 of 442), adjusted RR: 1.09, 95% CI: 0.96–1.23, P  =   0.179]. MRSA infection was not associated with increased length of hospital stay. Only 49% of MSSA bloodstream infections (BSI) received treatment with β-lactams, but appropriate definitive treatment was not associated with lower mortality (adjusted RR: 0.93, 95% CI: 0.70–1.23, P  =   0.602). Conclusions: MRSA-BSIs in Latin America are not associated with higher 30 day mortality or longer length of stay compared with MSSA. Management of MSSA-BSIs was not optimal, but appropriate definitive therapy did not appear to influence mortality.